2011
DOI: 10.1093/chemse/bjq134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Monell Forced-Choice, Paired-Comparison Tracking Procedure for Determining Sweet Taste Preferences across the Lifespan

Abstract: Lack of methodology to assess taste in children limits its measurement in research studies that include pediatric populations. We used the Monell 2-series, forced-choice tracking method to measure sucrose preferences of a racially/ethnically diverse sample (n = 949) of children, adolescents, and adults. Reliability was assessed by comparing the results of the first series with the second series. Validity was assessed by relating participants' sucrose preferences to their preferences for foods varying in sweetn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
145
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(173 citation statements)
references
References 39 publications
13
145
1
Order By: Relevance
“…The food-liking scale was developed for use in adults (21) and may not be appropriate for young children, who like higher concentrations of saltiness relative to adults (35) and are still in the neophobic stage of food acceptance (36). Because children have a strong biological inclination toward sweet taste (37,38), it also is possible that the drive for sweet taste limited the ability to detect salt-related dietary effects.…”
Section: Discussionmentioning
confidence: 99%
“…The food-liking scale was developed for use in adults (21) and may not be appropriate for young children, who like higher concentrations of saltiness relative to adults (35) and are still in the neophobic stage of food acceptance (36). Because children have a strong biological inclination toward sweet taste (37,38), it also is possible that the drive for sweet taste limited the ability to detect salt-related dietary effects.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 This method requires participants to taste pairs of sucrose solutions of varying concentrations (from 3% to 36%). After tasting each pair of solutions, the participants are asked to point to the solution they prefer.…”
Section: Choice Of Taste Stimuli For Use Inmentioning
confidence: 99%
“…Analyses confirmed that a single-series version of the task is sensitive to age effects, with children and adolescents demonstrating higher sucrose preferences than adults. 22 A single-series version of the assessment was thus selected as the NIH Toolbox gustation measure recommended for young children.…”
Section: Choice Of Taste Stimuli For Use Inmentioning
confidence: 99%
See 1 more Smart Citation
“…children have innate preferences for high levels of sweet [53] and salt [54]) and some individuals may be more sensitive to bitter tastes due to genotype [55], there is an inherent plasticity in the development of these chemical senses that interact with early-life experiences to ensure that a child is not restricted to a narrow range of foodstuffs because of innate preferences for and aversions to certain tastes [see ref. [56,57] for review].…”
Section: Complementary Food Introductionmentioning
confidence: 99%